Taa’t Al- Bazzi That are Preceded with a Madd Letter and Their Pedagogical Connotations in the Holy Quran - Abu Sa’ilik, Sanaa Suliman (Dirasat: Shari’a and Law Sciences, 2021)
This research tackles a phenomenon that Al-Bazzi’s recounted recitation of Quran from Ibn Kathir is concerned with. This phenomenon is concerned with geminating the Taa’at at the beginning of the present tense verb or the so-called Taa’t Al- Mutawa. The researcher used the inductive method to extrapolate the positions of the Taa’at preceded by a letter in the Holy Quran. The analytical method was alao used to analyze the opinions of the interpreters in directing the meanings and semantics of the Quranic verses, and the deductive method by deducing the educational semantics of the positions of these Taa’at where they are mentioned in the Quranic verses. The study concluded that the differences in the frequent readings of the Qur’an are evidence of the miracle of the Qur’an and the breadth of its meanings and provisions, and that the novel of Al-Bazzi with regard to the Taa’at Al-mudariyah is a model for the difference in frequent readings, and that any increase and difference in frequent reading undoubtedly adds meaning and leaves an impact. The study recommended directing the attention of researchers and scholars to reveal the educational connotations of the other two types of Al-Bazzi’s Taa’ats and directing the attention of researchers to study the connotations of the differences of frequent Quranic readings.